Brand equity and willingness to pay for condoms in zimbabwe - Snider Jeremy; Longfield Kim; Taruberekera Noah; Evans W Douglas (BMC, 2011)
Abstract Background Zimbabwe suffers from one of the greatest burdens of HIV/AIDS in the world that has been compounded by social and economic instability in the past decade. However, from 2001 to 2009 HIV prevalence among 15-49 year olds declined from 26% to approximately 14%. Behavior change and condom use may in part explain this decline. PSI-Zimbabwe socially markets the Protector Plus (P+) branded line of condoms. When Zimbabwe converted to a dollar-based economy in 2009, the price of condoms was greatly increased and new marketing efforts were undertaken. This paper evaluates the role of condom marketing, a multi-dimensional scale of brand peceptions (brand equity), and price in condom use behavior. Methods We randomly sampled sexually active men age 15-49 from 3 groups - current P+ users, former users, and free condom users. We compared their brand equity and willingness to pay based on survey results. We estimated multivariable logistic regression models to compare the 3 groups. Results We found that the brand equity scale was positive correlated with willingness to pay and with condom use. Former users also indicated a high willingness to pay for condoms. We found differences in brand equity between the 3 groups, with current P+ users having the highest P+ brand equity. As observed in previous studies, higher brand equity was associated with more of the targeted health behavior, in this case and more consistent condom use. Conclusions Zimbabwe men have highly positive brand perceptions of P+. There is an opportunity to grow the total condom market in Zimbabwe by increasing brand equity across user groups. Some former users may resume using condoms through more effective marketing. Some free users may be willing to pay for condoms. Achieving these objectives will expand the total condom market and reduce HIV risk behaviors.